2019
DOI: 10.20396/bjos.v18i0.8657271
|View full text |Cite
|
Sign up to set email alerts
|

Validity of self-report of oral conditions in older people

Abstract: Aim: To verify if self-report is a valid instrument to study the clinical oral condition in older people without cognitive deficit. Methods: A Cross-sectional study was conducted with 647 older people from the community, without cognitive deficit, living in Campinas, Brazil. A self-report questionnaire assessing the presence or absence of teeth (edentulism) and use of complete denture was applied, identifying the location of the denture, whether in the upper and/or lower arch. In the same session oral clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
6
0
3
Order By: Relevance
“…This method may represent a sensitive, practical, and efficient way to identify groups in which bad SRH could indicate an opportunity for intervention and for monitoring the impact of this intervention. 7 Furthermore, another FIBRA Study assessing the same volunteers as this study showed that self-reported oral condition is a valid measure for older people, reflecting their clinical oral condition, 40 therefore SRGH and SROH are both useful in epidemiological studies and primary care.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This method may represent a sensitive, practical, and efficient way to identify groups in which bad SRH could indicate an opportunity for intervention and for monitoring the impact of this intervention. 7 Furthermore, another FIBRA Study assessing the same volunteers as this study showed that self-reported oral condition is a valid measure for older people, reflecting their clinical oral condition, 40 therefore SRGH and SROH are both useful in epidemiological studies and primary care.…”
Section: Discussionmentioning
confidence: 76%
“…Besides, it has already been used in previous studies 39 and it keeps in line with previous research that we published on self-perceived health and selfperceived oral health as outcomes. 40 Self-rating is an effective and simple option that allows the physician to concentrate on the central problems of patients considering their life situation, determine their needs and expectations, 2 and employ ancillary personnel to collect information 32 . This method may represent a sensitive, practical, and efficient way to identify groups in which bad SRH could indicate an opportunity for intervention and for monitoring the impact of this intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, more epidemiological studies should be carried out in the future, considering the role of women as predictors of their male partners' oral health and the validity of the use of this information as an epidemiological oral health indicator. A study has shown that for older adults, individual self-perception is a valid form of assessment of their oral health condition, without the need for clinical evaluation [28]. When it is not possible for older adults to be examined by a health professional, their self-perception has been used due to its high degree of accuracy in relation to the actual oral situation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the prosthodontic condition such as partial edentulous space and removable partial prosthesis wearers also showed more risk or a negative view. Not only the questionnaire used in this study 10 but self-reporting in general may reflect in a validated form of the clinical oral condition in a Brazilian context, since people without cognitive deficit have accurately identified conditions such as edentulism and denture use 16 .…”
Section: Discussionmentioning
confidence: 99%
“…This cross-sectional study was performed in a University in Southern Brazil (Meridional Faculty -IMED), located in the city of Passo Fundo. The population of Passo Fundo is approximately 200,000 inhabitants 16 . Passo Fundo is a health reference in the State, and there are three Dental Schools with different types of treatment available for the population.…”
Section: Study Design and Locationmentioning
confidence: 99%